2022
DOI: 10.3389/fcvm.2022.967240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative pulse oximeter oxygen saturation on postoperative prolonged mechanical ventilation in patients with tetralogy of Fallot

Abstract: BackgroundAs an easily accessible and intervened clinical indicator, preoperative pulse oximeter oxygen saturation (SpO2) is an important factor affecting the prognosis of patients with tetralogy of Fallot (TOF). However, whether SpO2 is associated with postoperative mechanical ventilation (MV) time remains unknown. Therefore, this study aimed to investigate the impact of preoperative SpO2 on postoperative prolonged mechanical ventilation (PMV) in children with TOF.Materials and methodsThe study included child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A study from China, an upper middle-income country, observed that lower pre-operative saturations (median 82%, IQR 72–88 versus median 89%, IQR 81–95) were associated with poor outcomes [ 14 ]. In the Ethiopian study by Tefera et al, the median pre-operative saturation of patients who died was 76%, compared to 86% in survivors; however, the difference was not statistically significant [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study from China, an upper middle-income country, observed that lower pre-operative saturations (median 82%, IQR 72–88 versus median 89%, IQR 81–95) were associated with poor outcomes [ 14 ]. In the Ethiopian study by Tefera et al, the median pre-operative saturation of patients who died was 76%, compared to 86% in survivors; however, the difference was not statistically significant [ 9 ].…”
Section: Discussionmentioning
confidence: 99%